2020
DOI: 10.1039/d0ta01767a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin and defect-rich intermetallic Pd2Sn nanosheets for efficient oxygen reduction electrocatalysis

Abstract: Ultrathin and defect-rich Pd2Sn intermetallic nanosheets with unique Pd–Sn ordering are developed and display much enhanced activity and stability towards oxygen reduction in an alkaline medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…Furthermore, Li and co‐workers fabricated defect‐rich ultrathin intermetallic Pd 2 Sn nanosheets ( Figure a–c). [ 121 ] The as‐prepared ultrathin intermetallic Pd 2 Sn nanosheets presented excellent electrocatalytic performance for the ORR with a mass activity of 2.5 A mg −1 , which was higher than that of most Pd‐based composites reported to date (Figure 16d,e). Mechanistic studies revealed that the ligand effect caused by the thermodynamically stable intermetallic nanostructure significantly contributed to promoting electrocatalytic performance.…”
Section: Key Advantages Of 2d Pd‐based Nanocatalystsmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, Li and co‐workers fabricated defect‐rich ultrathin intermetallic Pd 2 Sn nanosheets ( Figure a–c). [ 121 ] The as‐prepared ultrathin intermetallic Pd 2 Sn nanosheets presented excellent electrocatalytic performance for the ORR with a mass activity of 2.5 A mg −1 , which was higher than that of most Pd‐based composites reported to date (Figure 16d,e). Mechanistic studies revealed that the ligand effect caused by the thermodynamically stable intermetallic nanostructure significantly contributed to promoting electrocatalytic performance.…”
Section: Key Advantages Of 2d Pd‐based Nanocatalystsmentioning
confidence: 83%
“…Although the ligand, strain, and interface effects promote the electrocatalytic performance of catalysts, the combination [121] Copyright 2020, Royal Society Chemistry.…”
Section: Summary and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…This strategy is also believed to show enormous potential to produce many other Pd‐based intermetallic nanostructures. Moreover, to the best of our knowledge the ultrathin two‐dimensional porous nanosheets with ordered atomic arrangement have rarely been reported, which are expected to show outstanding catalytic performance [6b] …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, curved lattice and fuzzy lattice can be observed in some regions, indicating the existence of lattice defects, which would be because of the diffusion of other atoms or Pd atoms′ migration in the Pd lattice. [14] Also, post TiO 2 modification, visible holes formed on the surface of Pd NS (Figure 1B1,B2). The dynamic light scattering (DLS) analysis was carried out to determine the size distribution of Pd NS and Pd@TiO 2 .…”
Section: Formation and Characterization Of Pd@tiomentioning
confidence: 93%